POTENSI ANAK USIA DINI MELALUI PENGEMBANGAN ASESMEN PENDIDIKAN KARAKTER - Palupi, Yulia (Universitas Muhammadiyah Magelang, 2016)
Children are generation that determines a nation’s future. Children’s characters formed from now on will determine the nation’scharacter in the future. Children’s characters will be formed well if in their development process they get sufficient chance toexpress themselves freely. Character education is taken important to be started in childhood as it is an educational processaimed to develop values, attitude and behavior which reflect good morality. Positive values which are supposed to be owned basedon character teaching are being pious, trustworthy, anticipative, positive-thinking, hard-working, civilized, dare to do right,dare to take risk, discipline, sincere, kind-hearted, godly, grateful, constructive, enthusiastic, initiative, responsible, tolerant,smart, careful, dynamic, cooperative, creative, independent, self- controlled, respectful to time, patriotic, friendly, compassionate,respectful to others’ works, assertive, diligent, humble, patient, having spirit of togetherness, open-minded, and tough in anysituation.